Analysis on joint operation non administrative accounting models of property development firms and the impact on taxation - Indar Khaerunnisa; Amrullah . (STIE Binaniaga, 2020)
This study aims to determine the accounting model in conducting joint operations (JO) by implementing non-administrative which consists of fix profit and percentage. Each fixed profit has three methods consisting of full revenue, profit sharing and PMK 261. The research used a descriptive qualitative method, with a case study approach. The study used primary data obtained from direct interviews with directly related parties conducting joint operations (JO or KSO). Meanwhile, the secondary data were obtained from the mutual agreement document and the financial report of the party conducting the joint operation (KSO). From the research results, it is obvious that the most recommended form of accounting is all forms according to PMK 261, both the fixed profit and percentage models. Keywords: Administrative Joint Operation, Non Administrative, Fixed Profit